Collapsibility behaviour of ABS P400 and PMMA used as sacrificial pattern in direct investment casting process - Shukri, Muhammad Shazwan (2017)
The feasibility of the Investment Casting (IC) process has been choose to be vital route in producing the metal alloy products. However, less report regarding the feasibility of portable Additive Manufacturing (AM) machines to be employed in casting process. Sacrificial wax pattern in casting process has been substitute with the AM material due to its brittleness and higher cost for hard tooling. Due to this constrain, the quality of fabricated AM materials, collapsibility analysis and strain induce was investigated. The patterns were made using ABS P400 and PMMA materials by two different types of technique which are Fused Filament Fabrication (FFF) and Polyjet technique. There were three different types of internal structures which are hollow, square and hexagon patterns. The thermal properties of the materials were studied by thermogravimetry analyzer (TGA) and linear thermal expansion. The collapsibility screening was determined to investigate the behavior of the patterns underneath the expansion. Apparently, patterns made by Polyjet technique shows better accuracy compare to FFF technique. It shows that, the PMMA error lies between -2.2 % until -0.63 % compared to ABS which is -2.4 % until 1.2% for hollow, square and hexagon patterns respectively. The data of the surface roughness were varies whereas internal structures does not play significant role in improving the surface roughness. From the strain analysis, it can be suggested that hexagon internal structure yield less stress compare to square patterns. In terms of collapsibility, hollow and hexagon patterns yield most successful warping whereas it indicates the patterns able to collapse underneath the expansion. Moreover, PMMA material tends to gain higher strain compared to ABS material whereas this can be illustrated by the graph of linear expansion. Nevertheless, to overcome the cracking of ceramic shell due to higher thermal expansion, different build layer thickness was adopted to overcome the issue.